Rates of Operative Management of Midshaft Clavicle Fracture in Adolescents Have Increased in Florida between 2005 and 2014. Issue 4 (November 2022) - Wu, Hao-Hua; Chopra, Aman; Carrillo, Laura A.; Callahan, Matt; Swarup, Ishaan
Background: It is not known if the adult literature on midshaft clavicle fracture treatment with open reduction internal fixation (ORIF) has influenced injury management in adolescents. Purpose : We sought to longitudinally evaluate the rates of operative management of adolescent midshaft clavicle fractures in the state of Florida. Methods : We conducted a retrospective review of data from the following Healthcare Cost and Utilization Project databases: the State Inpatient Database, the State Ambulatory Surgery and Services Database, and the State Emergency Department Database. Patients in Florida ages 10 to 18 years with midshaft clavicle fractures between 2005 and 2014 were identified along with data on age, sex, race/ethnicity, insurance type, treatment, and income percentile. We reviewed the data to identify trends in the rates of operative management of midshaft clavicle fractures. We then compared the rates of operative management between the first 3 years and the most recent 3 years (2005–2007 vs 2012–2014). Various demographic and socioeconomic factors were compared between patients treated with and without surgery. Descriptive statistics as well as univariate and multivariate analyses were performed. Results : There were 4297 midshaft clavicle fractures in adolescents identified between 2005 and 2014, and 338 (7.8%) of these fractures underwent operative management. There was a significant increase in the rate of operative management; it increased from 4.3% (n = 59) of the 1373 clavicle fractures that occurred between 2005 and 2007 to 11.2% (n = 130) of the 1164 clavicle fractures that occurred between 2012 and 2014. Patients with commercial insurance and patients who were older were more likely to undergo ORIF. Patients with Medicaid were more likely to undergo ORIF between 2012 and 2014 compared with patients with Medicaid between 2005 and 2007. Conclusions : Operative management rates of adolescent midshaft clavicle fractures have significantly increased in Florida over a decade; additional research is needed to understand these findings.